STRATEGI PENGEMBANGAN AGRIBISNIS PRODUK BUNGA KRISAN (Chrysanthenum indicum L) DI KABUPATEN KARO - Royjon Sinaga; Lyndon Parulian Nainggolan; Kiki PS Munthe (Universitas Quality, 2020)
The study was done to see how chrysanthemum flower products developed from the way chrysanthemum flower production and marketing was developed. To know internal and external strategies and swot analysis support the development of chrysanthemum products in Karo regency. Adhesive control of research areas. The sample is a goatherd, a farm group, a chief of the service who endear the farm service, a goat merchant, and an entire agency of Suka village. Data retrieval through interview, documentation and observation questionnaire. The result of the study are internal factor : Stregth (natural resourches, human resourches, security strive) Weakness (limited markets, limited land, lack of government support), External factor : Opportunities (regional auotnomy, chrysanthemum flower derivatives, markets that are open locally and abroad, opening up new agrotourism) Threats (pests and disease, competitor flowers, chrysanthemum price fluctuations) and strategy of a swot matrix, which is to improve the natural resourches quality through training and expand its chrysanthemum farm effort, increase productivity and the quality of chrysanthemum flower and their markets, increase productivity and the quality of chrysanthemum flower to be able to compete with foreign market, open up new agrotourism with the support of natural resourches and regional autonomy.